Corpos que acontecem na fronteira - Shahd Wadi (e-cadernos ces)
Palestine is a symbol of exile. In a way, all Palestinians live in a state of literal or metaphorical exile. For this reason, it is impossible to analyze Palestinian women’s cinema without locating these women in their (non)place: exile. In this article I discuss films of women screenwriter-directors who live outside Palestine: Salt of This (2008), by Annemarie Jacir, and Amreeka (2009), by Cherien Dabis. I question how both protagonists and simultaneously how both screenwriters-directors, try to (un)define the notion of home, exile, and border. I ask whether these women managed to find a place of their own through their bodies in film.